2008
DOI: 10.1016/j.margeo.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous sea-floor backscatter patterns in methane venting areas, Dnepr paleo-delta, NW Black Sea

Abstract: The relation between acoustic seafloor backscatter and seep distribution is examined by integrating multibeam backscatter data and seep locations detected by single-beam echosounder. This study is further supported by side scan sonar recordings, high-resolution 5 kHz seismic data, pore-water analysis, grain-size analysis and visual seafloor observations. The datasets were acquired during the 2003 and 2004 expeditions of the EC-funded CRIMEA project in the Dnepr paleo-delta area, northwestern Black Sea.More tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 66 publications
(107 reference statements)
2
56
0
Order By: Relevance
“…The parameter χ, introduced in previous works and emphasized in Section 3.1, provides a way to quantify the importance not only of the average grain size, but also of its distribution [42][43][44]. Equation (1) shows that it is easy to estimate from the granular medium or soil granulometry. From its other formulation (Equation 2), it is possible to link it with the Bond number, as χ = w/Bo, where w is the relative variation of the pore size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter χ, introduced in previous works and emphasized in Section 3.1, provides a way to quantify the importance not only of the average grain size, but also of its distribution [42][43][44]. Equation (1) shows that it is easy to estimate from the granular medium or soil granulometry. From its other formulation (Equation 2), it is possible to link it with the Bond number, as χ = w/Bo, where w is the relative variation of the pore size.…”
Section: Discussionmentioning
confidence: 99%
“…It includes a large variety of phenomena such as methane venting [1], hydraulic fractures [2][3][4], pockmarks [5][6][7], hydrothermal complexes [8,9], kimberlite pipes [10][11][12] or mud volcanoes [13][14][15][16]. Since the 90's, the technique of air sparging has also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Gas invasion in an immersed granular layer is a widespread phenomenon of striking importance in many contexts, from oil industry [1,2] to soil decontamination, where air injection in the subsurface and its subsequent rising by buoyancy removes or chemically degrades the contaminants [3]. In natural processes, piercement structures display many examples of such phenomenon [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the presence of free gas in the subsurface sediments (first ~ 20 cm) influences the acoustic properties of the sediment amplifying the energy scattering because of the increased acoustic impedance (e.g. Boyle and Chotiros, 1995;Fonseca et al, 2002;Hagan and Vogt, 1999;Naudts et al, 2008;Sweeney et al, 2012), although, Fonesca et al (2002 postulated that in shallow water the presence of free gas in the subsurface sediments reduces the backscatter intensity due to the decrease in sediment sound speed. High-resolution reflection seismic systems are significantly affected by the presence of shallow gas and are commonly used for the detection of free gas in sediments (e.g.…”
Section: High Backscatter On the Slope Of The Lobementioning
confidence: 99%